The Characteristics of Crackers Made from Formulation of Wheat and Modified Water Yam Flour - Rosida, Rosida; Susiloningsih, Enny Karti Basuki (Universitas Dr Soetomo, 2020)
The previous study showed that combination of wheat flour (70%) and modified water yam flour (30%) produced crackers which had the best characteristics. In this research, the effect of formulation of wheat and three kind of modified water yam flour on Resistant Starch (RS) content and Glycaemic index of the crackers were studied. Modified water yam flour was made from purple, white, and yellow ones which had been treated by three cycles autoclaving-cooling process. The native water yam flour, without treatment with autoclaving, were used as comparison. The result showed that sample crackers had higher resistant starch (1.67 -3.65%) and dietary fiber (16.65 -18.41%) content, compared to standard crackers from wheat flour. Furthermore, the crackers from modified yam flour with white water had the lowest GI (34.13) comparing with other crackers. So it could be developed as functional food for preventing diabetes mellitus or other digestive tract disrupter.